Does parenting disciplinary practices affect social behavior of children enroll in child care centres: effect of quality child care - Janon, Nazariah Shar'ie; Syed Alwi, Sharifah Maisarah (2013)
This study examined the influence of parenting disciplinary practices on social behavioral outcomes of children who attend child care centre. The study also attempted to investigate whether the relationship between parenting disciplinary practices and children’s social behavior vary with respect to the quality of child care centre. It hypothesized that parenting disciplinary practices influence children’s social behavior and the relationship is moderated by the quality of child care centre. 112 parents of children aged 4-6 year old who attend child care centers around Kuala Lumpur and Selangor participated in this study. Data collected via survey and observations using measures such as Caregiver Interaction Scale [CIS] (Arnett, 1989), Strength and Difficulty Questionnaire [SDQ] (Goodman, 1997) and Parenting Scale [PS] (Rhoades & O’Leary, 2007). Results indicated that ineffective parenting disciplinary practices significantly affect children’s social problems. The results, however, did not show the moderating effect of quality child care. Thus, parenting disciplinary practices is a significant predictor of social behavior of children in child care and it did not moderate by quality child care. These findings are discussed in relation to current issues within the literature on child care, family and child development.